Genomic signals of ecogeographic adaptation in a wild relative are associated with improved wheat performance under drought stress - Nyine, M.; Davidson, D.; Adhikari, E.; Clinesmith, M.; Wang, H.; Akhunova, A.; Fritz, A.; Akhunov, E. (2025)
Background Prioritizing wild relative diversity for improving crop adaptation to emerging drought-prone environments is challenging. Here, we combine the genome-wide environmental scans (GWES) in wheat diploid ancestor Aegilops tauschii (Ae. tauschii) with allele testing in the genetic backgrounds of adapted cultivars to identify diversity for improving wheat adaptation to water-limiting conditions.